Peran Harga, Iklan dan Pelayanan terhadap Keputusan Pembelian - Ratu Neneng Rozbiati; Soleh . (The Asia Pacific Journal Of Management Studies, 2014)
The purpose of this research was to examine empirically the effect between price, advertising and Service on customer decision among the employees at Bank Rakyat Indonesia in Rangkasbitung. 100 customers selected as samples by using simple random sampling technique taken from the overall population of 134 customers. The effect technique was applied to analyze the data which had been previously treated with the regressive and correlation procedure. The result proved that the customer decision was positively affected by the price, advertising and service at Bank Rakyat Indonesia in Rangkasbitung, and the service was positively affected by the price and the advertising. The findings suggest that the variation of the customer decision of the customers might have been affected by the price, advertising and the Service.